Spatiotemporal Analysis of the Prevalence and Pattern of Multimorbidity in Older Chinese Adults - Chen, Shimin; Wang, Shengshu; Jia, Wangping; Han, Ke; Song, Yang; Liu, Shaohua; Li, Xuehang; Liu, Miao; He, Yao (Frontiers in Medicine, 2022)
Background: Multimorbidity posts an enormous problem to societal and healthcare utilization under the context of ageing population in low- and middle-income countries (LMICs). Currently, the systematic studies on profile of multimorbidity and its characteristics among Chinese elderly are lacking. We described the temporal and spatial trends in prevalence of multimorbidity and explore chronological changes of comorbidity pattern in a large elderly population survey. Methods: Data was extracted from Chinese Longitudinal Healthy Longevity Study (CLHLS) conducted between 1998 and 2018 in randomly selected about half of the counties and city districts. All the elderly aged 65 and older were included during the 8 waves survey. We used 13 investigated chronic diseases to measure the prevalence of multimorbidity by geography, subpopulation and chronological changes. The patterns of multimorbidity were assessed by computing the value relative risk (RR) and observed-to-expected (O/E) ratio. Results: From 1998 to 2018, prevalence of multimorbidity went from 15.60% to 30.76%, increasing with fluctuation across the 8 survey waves (P for trend=0.020). The increasing trends were observed similarly in the different gender group (P male=0.009; P female=0.004) and age groups among female participants (P~80=0.009; P81~90=0.004; P91~100=0.035; P101~=0.018). The gap in prevalence of multimorbidity between the north and the south were getting narrow across the 8 survey waves. Hypertension was the highest prevalent chronic condition while diabetes has the highest RR determined for the 13 kinds of chronic conditions in CLHLS survey. The most frequently occurring clusters were hypertension and heart disease, hypertension and cataract, hypertension and chronic lung disease. And cancer, tuberculosis and Parkinson’s disease cluster took the domination of O\E rankings over time. Conclusions: The prevalence of multimorbidity has been increasing nationwide and more attention should be paid to the rapid growth in the southern part of China. It demands the effective diagnosis and treatment adopted to the highly prevalent comorbidities, and strategies and measures adjusted to strongly relevant clusters. Implications for those countries or regions that are experiencing the early stage of rapid economic development and aging, primary prevention and health management of lifestyle and chronic diseases should be emphasized.